(untitled) (Circe de clásicos y modernos, 2018)
This paper reflects on some aspects concerning on the combat between translators and interpreters of Holy Scripture when they must translate and decode its right sense. The first part, in a descriptive way, consists of the necessary presentation of the Septuagint production context and the values it had for both Jews and Christian authors. The second one focuses on Ambrose of Milan’s position about the disposition and fervour that the holy text apprehension requires in a Christian view.